1999
DOI: 10.1143/jpsj.68.3770
|View full text |Cite
|
Sign up to set email alerts
|

Structural Phase Transition in (NMe4)2TCNQ3

Abstract: The structural properties of a neutral/radical 1 : 2 mixed compound, (NMe 4 ) 2 TCNQ 3 , have been studied by the X-ray diffraction method in a temperature range between 25 and 150 °C. The experimental data show that a second order phase transition takes place at around 60 °C and that the high-temperature phase has a monoclinic C2/m structure. The molecular planes of dimerized TCNQ -⋅ radicals, being slipped against each other in the low temperature phase, are expected from the C2/m symmetry to be totally ecli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This component couples with the molecular vibration to drive the EMV modes, which appear along the E//a polarization with much smaller intensity compared to the modes appear in E//b polarization. We have previously observed in the case of (NMe 4 ) 2 TCNQ 3 , which crystal structure is very similar to the present substance, that these modes disappear when the TCNQ − dimers are no longer slipped due to the phase transition [17,19]. The intensity of the EMV modes appear in E//a polarization, therefore, represents the amount of slip distance of the TCNQ − dimers.…”
Section: Discussionsupporting
confidence: 87%
“…This component couples with the molecular vibration to drive the EMV modes, which appear along the E//a polarization with much smaller intensity compared to the modes appear in E//b polarization. We have previously observed in the case of (NMe 4 ) 2 TCNQ 3 , which crystal structure is very similar to the present substance, that these modes disappear when the TCNQ − dimers are no longer slipped due to the phase transition [17,19]. The intensity of the EMV modes appear in E//a polarization, therefore, represents the amount of slip distance of the TCNQ − dimers.…”
Section: Discussionsupporting
confidence: 87%
“…(1) to the experimental data yields T C = 340 K, and α = 0.62-0.70 for all the bands. The values of α are compared with α = 0.63 and 0.66, which are obtained for the intensity of the S 1 band and (018) Bragg reflection of the X-ray diffraction, respectively [2,3].…”
Section: Methodsmentioning
confidence: 99%
“…A structural phase transition in this substance was suggested from the temperature dependence of the satellite band (S 1 ) observed at 1.3 eV in the E//a polarization of the optical absorption spectrum, where E and a are the electric field of light and a-axis of the monoclinic crystal structure, respectively [2]. The S 1 band diminishes continuously with increasing temperature to disappear at T C = 65 o C. The Xray diffraction study has shown that second-order structural phase transition takes place at the same temperature [3]. In the low-temperature phase the two TCNQ anion radicals form a slipped dimer, in which they are displaced against each other in the direction of short molecular axis.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the dipole moment of the charge transfer transition is not perfectly parallel to the b-axis but is slightly canted to have a weak component along the a-axis, and thus drives the S 1 abd emv bands for the Ella polarization. As temperature is elevated the second order phase transition takes place at 338 K to have the TCNQ − molecules be completely eclipsed [11], so that above 338 K both the S 1 and emv bands disappear for Ella. In this analogy, the present experimental result suggests strongly that the radical-like TCNQ − molecules are eclipsed in the high-pressure phase of Cs 2 TCNQ 3 .…”
Section: Discussionmentioning
confidence: 99%